Electronic Patient Records in Interprofessional Decision Making: Standardized Categories and Local Use - Winman, Thomas; Rystedt, Hans (Human Technology, 2012)
Electronic patient records (EPRs) are a constitutive element of medical practice and are expected to improve interprofessional communication and support decision making. The aim of the current study is to explore the ways in which access to structured information from multiple professions within EPRs enters into the phases involved in arriving at final agreements about patients' future care. The results show that decision making in interprofessional team rounds involves a prestructuring of a pathological reality. Further, the results demonstrate how information in EPRs is deconstructed and recast into patterns that presuppose knowledge about the EPR's structural organization. This means that EPRs are highly flexible technologies and that their design does not determine their usefulness. A major conclusion is that the members' knowledge on how to bridge between standardized categories in EPRs and their local meanings is decisive for understanding the basic conditions necessary for how EPRs could support interprofessional collaboration.